2023
DOI: 10.3390/nu15020331
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of MED-01 Probiotics on Vaginal Health: A 12-Week, Multicenter, Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Bacterial vaginosis (BV) is the most common disease in women of childbearing age and is caused by the growth of abnormal microbiota in the vagina. Probiotic consumption can be an effective alternative treatment to preserve or improve vaginal health. In the present study, MED-01, a complex of five strains of probiotic candidates isolated from the vagina of Korean women, was used. This study was designed as a 12-week, randomized, multicenter, double-blind, placebo-controlled clinical trial to evaluate the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The consequent analyses confirmed the increment of L. plantarum, concomitant with inhibiting harmful bacteria such as Mobiluncus spp., Gardnerella vaginalis, and Atopobium vaginae. This clinical trial demonstrated that this probiotic complex can be used for treating BV, as it improves the vaginal microbiota (Park et al, 2023).…”
Section: Probiotics In the Treatment Of Urogenital Infectionsmentioning
confidence: 80%
“…The consequent analyses confirmed the increment of L. plantarum, concomitant with inhibiting harmful bacteria such as Mobiluncus spp., Gardnerella vaginalis, and Atopobium vaginae. This clinical trial demonstrated that this probiotic complex can be used for treating BV, as it improves the vaginal microbiota (Park et al, 2023).…”
Section: Probiotics In the Treatment Of Urogenital Infectionsmentioning
confidence: 80%
“…The general characteristics of the included studies are outlined in Table S4. Trials were published between 1996 and 2023, and were carried out in Asia, 12,27–31,77–81,84–229 Europe, 230–262 America,…”
Section: Resultsmentioning
confidence: 99%
“…In total, 12,603 participants (6507 case subjects and 6096 control subjects) with ages ranged from 18 to 82 years and baseline BMI ranged between 19.1 and 38.76 kg/m 2 . Twenty‐six studies investigated the effects of probiotics and/or synbiotics in healthy subjects, 111,118,141,144,146,148,155,161,171,180,191,192,195,200,201,207,219,232,235,237,240,241,247,260,265,272 and the remaining studies enrolled unhealthy participants. All the studies were performed in both genders, whereas seven studies conducted on males 192,224,229,239,260,265,272 and 30 studies were on females 12,27,85,103,105,120,129,133,158,161,162,188,191,197,203,206,210,216,218,221,222,227,235,237,248,254,256,259,262,264 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering probiotic interventions for vaginal health, it is essential to select probiotic strains with proven efficacy and safety profiles Lactobacillus (Lacticaseibacillus rhamnosus MG4288, Lactiplantibacillus plantarum MG989, Lacticaseibacillus paracasei MG4272, Ligilactobacillus salivarius MG242, and Limosilactobacillus fermentum MG901 species are the most used probiotics for vaginal health (Park et al 2023).…”
Section: Probiotic Interventions: Strategies For Harmonizing the Vagi...mentioning
confidence: 99%